Réflexions sur la restauration du patrimoine paléontologique à travers la réhabilitation scientifique d'un fossile d'ichthyosaure - Romanella Bosseau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The restoration of an ichthyosaur fossil (Lias, Holzmaden) as post-graduate work has shown relevance of a specific, multiple approach when dealing with this type of piece. Since the fossil is at the same time a paleontological tool, a cultural asset and a historical collection “object”, we chose to carry out a scientific rehabilitation. The article describes our approach, the balance that was achieved among all three dimensions and the imperatives related to the conservation of the fossil.